Ofèlia Dracs i la recepció d'H.P. Lovecraft a la literatura catalana. - Garvin, Mario (Zeitschrift für Katalanistik, 2025)
The book of short stories Lovecraft, Lovecraft! (1981) by the Catalan collective Ofèlia Dracs has been harshly judged by critics for failing to reach the tone and level of H.P. Lovecraft's stories. This paper suggests that such judgments have been made on the basis of two false postulates. First, it has been interpreted that the purpose of this volume was to pay homage to Lovecraft, when in fact, as defended here, the purpose was to write horror stories, a genre that is hardly cultivated in Catalan literature and that the Ofèlia Dracs collective intends to promote. Secondly, these stories have been evaluated as if they had been written by a single author, when in fact they are the work of ten individual authors. A specific analysis of each of the stories shows the ways in which each of the authors tried to contribute to this collective purpose, concluding that the volume deserves a place in the history of the horror genre in Catalan literature.